2008
DOI: 10.1542/peds.2007-2849
|View full text |Cite
|
Sign up to set email alerts
|

Child Versus Adult Research: The Gap in High-Quality Study Design

Abstract: In 6 leading generalist and specialist journals, studies involving adults were significantly more likely than child studies to be randomized, controlled trials, systematic reviews, or studies of therapies. If such studies are to be viewed as the highest possible quality of evidence, then this difference has implications for quality of care for children and for funding and future directions in clinical research involving children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 20 publications
(17 reference statements)
1
60
2
4
Order By: Relevance
“…Recent advances in multicentre cancer trials in children have increased childhood cancer 5 year survival from 28% in the late 1960s to 79% by 2005 [10][11][12][13]. Regrettably, these stories of remarkable benefits cannot be extended to many other childhood conditions [14] because of the dearth of relevant trials.…”
Section: Imperative To Conduct Trials In Childrenmentioning
confidence: 99%
“…Recent advances in multicentre cancer trials in children have increased childhood cancer 5 year survival from 28% in the late 1960s to 79% by 2005 [10][11][12][13]. Regrettably, these stories of remarkable benefits cannot be extended to many other childhood conditions [14] because of the dearth of relevant trials.…”
Section: Imperative To Conduct Trials In Childrenmentioning
confidence: 99%
“…We arbitrarily chose to select a random sample of 35% of the PRCTs published in 2006, in keeping with an earlier study, [20] instead of a 3-month sample. [11] We used a computer-based random selection strategy stratified on journal category. This strategy selected 31 articles in GMJs, 60 in PMJs, and 53 in SMJs (144 articles in all).…”
Section: Literature Searchmentioning
confidence: 99%
“…A review of articles published in 2005 in six leading general and specialist journals showed that studies performed in adults were significantly more likely than paediatric studies to be RCTs, systematic reviews, or studies of therapeutic interventions. [11] Compared to studies in adults, studies in paediatric patients are fewer, less well designed, and less well reported. [12] In addition to this previously described paucity of high-quality paediatric studies, we found that few paediatric studies focused on the youngest patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations